Transformative Potential of Friluftsliv in Physical Education: Insights From an International Student Programme - Lisa Lefèvre; Christophe Schnitzler; Hakon Engstu; Mary Schirrer (Australian Journal of Environmental Education)
Friluftsliv is a Scandinavian concept that emphasises a deep connection with nature through outdoor activities. This study examines its transformative role in fostering physical literacy and environmental ethics among international students. The University of South-East Norway offers a year-long programme that integrates theoretical coursework with outdoor experiential learning, including multi-day expeditions, exemplifying embodied pedagogy. Students were observed for one week, and at its conclusion participated in creative focus groups where they discussed and illustrated their most memorable experiences. The winter expedition emerged as a clear highlight. Analysis of interviews and artwork revealed that the teaching methods used enhanced students’ skills, knowledge, social connections, and motivation to engage with nature, thus reinforcing the four pillars of physical literacy. It also fostered a significant emotional transformation. While students initially approached nature from an anthropocentric perspective, the challenges of the winter trip, in particular, helped most of them to shift their outlook towards a more ecocentric view by deepening their connection with the natural environment. This study highlights the powerful role that experiential outdoor education can play in cultivating both physical literacy and environmental stewardship.